The implementation of Taguchi method on EDM process of Tungsten Carbide - Lajis, Mohd Amri; Che Daud, Mohd Radzi; Amin, A. K. M. Nurul (EuroJournals Publishing, Inc., 2009)
In this paper, the cutting of Tungsten Carbide ceramic using electro-discharge machining (EDM) with a graphite electrode by using Taguchi methodology has been reported. The Taguchi method is used to formulate the experimental layout, to analyse the effect of each parameter on the machining characteristics, and to predict the optimal choice for each EDM parameter such as peak current, voltage, pulse duration and interval time. It is found that these parameters have a significant influence on machining characteristic such as metal removal rate (MRR), electrode wear rate (EWR) and surface roughness (SR). The analysis of the Taguchi method reveals that, in general the peak current significantly affects the EWR and SR, while, the pulse duration mainly affects the MRR. Experimental results are provided to verify this approach.